An effective and sustainable approach for achieving self-healing in nitrile rubber. (5th October 2020) - Utrera-Barrios, Saul; Araujo-Morera, Javier; Pulido de Los Reyes, Laura; Verdugo Manzanares, Reyes; Verdejo, Raquel; López-Manchado, Miguel Ángel; Hernández Santana, Marianella
Graphical abstract: Highlights: Carboxylated nitrile rubber (XNBR)-ground tire rubber (GTR) compounds were prepared. GTR was grafted with acrylic acid (AA) increasing self-healing of XNBR up to 70%. Carboxylic groups from AA in GTR and XNBR form ionic interactions with ZnO. The incorporation of GTR maintained the chemical resistance of XNBR. The use of waste material like GTR opens a path for sustainable material design. Abstract: Nitrile rubber is considered the workhorse of the automotive rubber industry, thanks to its chemical resistance and mechanical performance. However, applications such as hoses, seals or gaskets are prone to damage, limiting their lifetime. In this work, carboxylated nitrile rubber (XNBR) was ionically crosslinked with zinc oxide (ZnO), forming ionic domains grouped into ionic clusters. These clusters have the advantage of being reversible under the application of an external stimulus such as temperature, conferring the material a certain self-healing capability and enabling a lifecycle extension. Ground tire rubber selectively modified by grafting of poly(acrylic acid) (gGTR), was added to XNBR-ZnO compounds with the aim of improving the healing properties of the rubber matrix. The incorporation of acid groups contributed to the formation of additional ionic clusters during the crosslinking process, resulting in a notorious increase in healing efficiency from 15% for the XNBR-ZnO to 70% for the XNBR-ZnO-gGTR compound. Chemical and mechanical resistance were also evaluated, showing that the addition of a waste material like gGTR keeps mechanical strength suitable for many applications; meanwhile, it does not deteriorate its resistance to aliphatic solvents such as motor oil and gasoline. These promising results open the path for developing sustainable rubber products with extended lifetime and applicable within the automotive industry.